2010
DOI: 10.1029/2010jd013929
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of the heterogeneous reaction between O3(g) and halides at the surface of frozen salt solutions

Abstract: [1] Springtime ozone depletion events have been linked to elevated levels of bromine in the polar boundary layer. It has also been suggested that iodine may play an important role in boundary layer chemistry. However, the mechanism(s) for initial halogen activation is not well understood. We report results of experiments using glancing-angle laser-induced fluorescence (LIF) and glancing-angle Raman spectroscopy to investigate the heterogeneous reaction of gas-phase ozone with bromide and iodide ions at the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 38 publications
2
47
1
Order By: Relevance
“…Takenaka et al (1992) discarded any catalytic properties of the ice surface to produce this acceleration. The dependence of the rate on the enhanced concentration due to the volume of liquid brine reduction during freezing was later confirmed (Finnegan, 2001;Takenaka and Bandow, 2007;Grannas et al, 2007a;Wren et al, 2010). This conclusion holds for soluble species and bimolecular (or higher-order) reactions.…”
Section: Freeze-concentration Effectmentioning
confidence: 73%
“…Takenaka et al (1992) discarded any catalytic properties of the ice surface to produce this acceleration. The dependence of the rate on the enhanced concentration due to the volume of liquid brine reduction during freezing was later confirmed (Finnegan, 2001;Takenaka and Bandow, 2007;Grannas et al, 2007a;Wren et al, 2010). This conclusion holds for soluble species and bimolecular (or higher-order) reactions.…”
Section: Freeze-concentration Effectmentioning
confidence: 73%
“…The authors concluded that dissociation of acids may occur within the DI. The release of hydroxide anion in the heterogeneous ozonation of bromide at sea-ice surfaces was also confirmed using harmine, another pH-sensitive fluorescent probe (Wren et al, 2010).…”
Section: Frozen Aqueous Solutionsmentioning
confidence: 75%
“…Donaldson and coworkers compared the air-ice and airwater interfaces using Raman spectroscopy at glancing angle of the OH-stretch bands. The protonation of acridine, an organic fluorescent pH probe, at the air-ice interface was observed in the presence of HNO 3 or HCl deposited to the ice surface from vapors (Kahan et al, 2007;Wren and Donaldson, 2012). However, no enhancement in the proton concentration was observed at the interface upon freezing mildly acidic or neutral solutions.…”
Section: Frozen Aqueous Solutionsmentioning
confidence: 98%
“…However, if a concentrated liquid brine exists at the surface of frozen salt solutions, as well as within the liquid inclusions present in the iced matrix, one might expect the reaction kinetics to be similar to those in aqueous solution. In fact, recent measurements of the heterogeneous ozonation kinetics at the surface of frozen NaBr and NaI solutions (Wren et al, 2010) show kinetics which are consistent with the reaction occurring in concentrated aqueous solutions. In the present study, we measure photolysis kinetics of an organic probe molecule in aqueous solution and at the surfaces of frozen freshwater and salt solutions to determine whether the reaction environment at the surface of frozen salt solutions is more similar to a QLL or to aqueous solution.…”
Section: Introductionmentioning
confidence: 77%
“…The LLG was positioned approximately 7 mm above the sample. This geometry affords us surface sensitivity , and allows us to measure kinetics at air-ice interfaces , 2008Kahan et al, 2010a, b;Wren et al, 2010).…”
Section: Methodsmentioning
confidence: 99%